Respuesta :

2x+4(2x+7)=3(2x+4)

2x+8x+28=6x+12

10x+28=6x+12

4x+28=12

4x=-16

x=-4

Answer:

4x²+20x+16=0

Step-by-step explanation:

First we can expand the right side:

[tex](2x+4)(2x+7) = 4x^{2} +8x+14x+28[/tex]

Simplify:

[tex]4x^{2} +26x+28[/tex]

Now we can expand the left side:

[tex]3(2x+4) = 6x+12[/tex]

Now we equate both of them to each other:

[tex]4x^{2} +26x+28= 6x+12[/tex]

To make this into a quadratic form we can subtract 6x+12 from both sides:

[tex]4x^{2} +26x+28 - (6x+12) = 6x+12- (6x+12)[/tex]

Simplify

[tex]4x^{2} +20x+16 = 0[/tex]

This is the equation in most simplified version.